AN EVALUATION OF MERDEKA STUDENT EXCHANGE PROGRAM FOR EFL INBOUND STUDENTS: A QUALITATIVE STUDY - Arit, Elisabeth; Naura, Salwa; Apoko, Tri Wintolo (Indonesian Journal of Educational Development (IJED), 2024)
This study aims to evaluate the Merdeka Student Exchange Program for EFL inbound students at Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA). Using a qualitative phenomenological approach, this study explores the subjective experiences of exchange students while participating in the program. Data were collected through semi-structured interviews with six inbound students from different universities in Indonesia. The findings revealed two main themes: challenges and benefits. Challenges included adjusting to a new environment, cultural differences, and communication styles. Students also reported several benefits, such as meeting new people from different backgrounds, exploring new places, and experiencing a different classroom environment with different teaching methods and facilities. Significantly, students experienced personal growth through an increased understanding of global diversity, intercultural skills, and the development of qualities such as critical thinking, adaptability, and openness to difference. These findings are consistent with the literature highlighting the personal development of student exchange programs. The Merdeka Student Exchange Program at UHAMKA was proven to be a valuable initiative in promoting academic mobility, enhancing students' skills and knowledge, and fostering personal development. This research confirms the importance of exchange program in preparing students to become qualified global citizens capable of navigating the complexities of an interconnected world.